SPECULATIONS IN SCIENCE FICTION AND THEIR IMPLEMENTATION IN REAL SCIENCE - Andrew Lessard (TADQIQOTLAR.UZ, 2024)
Abstract. The article analyzes the influence of the ideas of science fiction writers on the development of real science. Examples are given about the introduction of fantastic concepts into modern scientific theories and technologies. The importance of science fiction as a source of inspiration for scientists and engineers is discussed.